Extraction of Unerupted Maxillary Canine Teeth in a Maned Wolf (Chrysocyon brachyurus) - Lourdes M. B. Pessoa; Marcello Roza; Anderson Farias; Pedro Henrique de Jesus; Rita de Cassia Campbell; Mariângela Pereira de Pinho (Case Reports in Veterinary Medicine)
The purpose of this case report is to describe the diagnosis and treatment of unerupted canine teeth in a maned wolf. After physical examination, complete blood count, and serum biochemical profile, the animal underwent general anesthesia and head radiography was performed to confirm the diagnosis. The treatment consisted of the extraction of both maxillary canine teeth and clinical and radiographic follow-up of the right mandibular canine tooth.